Does exposure to socially endorsed food images on social media influence food intake?. (1st October 2021) - Hawkins, Lily; Farrow, Claire; Thomas, Jason M.
Abstract: Social norms can influence the consumption of high and low energy-dense (HED/LED) snack foods. Such norms could be communicated via social media, however, there is little experimental research investigating this possibility. This laboratory study aimed to investigate the acute effect of socially endorsed social media posts on participants' eating behaviour. Healthy women students ( n = 169; mean age = 20.9; mean BMI = 23.3) were assigned to either a HED, LED or control condition, where they viewed three types of images (HED foods, LED foods and interior design as control), but only one type was socially endorsed (e.g. in the control condition, only interior design images were socially endorsed). Participants completed questionnaires and were also provided a snack buffet of grapes and cookies. One-way ANOVA revealed a significant main effect of condition on participants' relative consumption of grapes (percentage of grapes consumed out of total food intake), for both grams and calories consumed (both p s < .05). Follow-up t-tests revealed that participants consumed a larger proportion of grapes (grams and calories) in the LED condition vs HED condition (all p s < .05), and a larger proportion of calories from grapes in the LED compared to control condition ( p < .05). These findings suggest that exposure to socially endorsed images of LED food on social media could nudge people to consume more of, and derive more calories from these foods in place of HED foods. Further research is required to examine the potential application of these findings.